PEMETAAN RELIGIOSITAS SEBAGAI BAGIAN DARI MODEL PENGELAKAN PAJAK PADA PELAKU UMKM DI INDONESIA: PEMETAAN RELIGIOSITAS SEBAGAI BAGIAN DARI MODEL PENGELAKAN PAJAK PADA PELAKU UMKM DI INDONESIA - Kuntaryanto, Oki; Jati, Agung Nugroho; Purwanti, Titik (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2023)
This study aims to map religiosity in the tax evasion model. Using the survey method, the questionnaire was distributed to MSME actors in Indonesia. This study used random sampling (random sampling). The samples collected and the data ready to be processed were 132. The moderating effect in the model was processed using the moderated regression analysis technique. The results of this study are that religiosity does not moderate the influence of culture and income on tax evasion. Future research can use demographic variables as control variables to get more robust results.